Could trans-vaginal sono-elastography help benign-malignant differentiation of cervical masses? - Magda Shady (The Egyptian Journal of Radiology and Nuclear Medicine, 2015)
Aim: To determine role of trans-vaginal sono-elastography in differentiation between normal and diseased cervix and whether strain ration can be used for characterization of cervical carcinoma in postmenopausal women. Patients and methods: From January 2012 to October 2013, seventy consecutive postmenopausal women were examined by trans-vaginal elastography. The 70 women included: (1) control group (30 healthy women) and (2) diseased group (40 patients). Pathological results were used as the gold standard. Strain ratios were calculated and compared between normal (control) and abnormal (diseased) cervix, also between benign and malignant lesions. The accuracies of SR in differentiating benign and malignant cervical lesions were assessed with the Student’s t test and receiver operating characteristic curve (ROC) analysis. Results: There was statistically difference in mean SR between normal and abnormal cervix and between malignant and benign cervical lesions (p < 0.0001 and p < 0.0001 respectively). SR of 3.4 resulted in 100% sensitivity, 100% specificity and 100% accuracy for differentiation between normal and diseased cervix. SR of 8.7 resulted in 93.8% sensitivity, 100% specificity and 95% accuracy in differentiation between malignant and benign cervical lesions. Conclusion: TV sono-elastography is a useful technique in differentiation between normal and abnormal cervix and between malignant and benign cervical lesions.